Synthesis of Fluorescent PMMA‐Based Nanoparticles. Issue 7 (28th August 2012) - Dossi, Marco; Ferrari, Raffaele; Dragoni, Luca; Martignoni, Carlotta; Gaetani, Paolo; D'Incalci, Maurizio; Morbidelli, Massimo; Moscatelli, Davide
Abstract The synthesis of PMMA‐based nanoparticles (NPs) covalently labeled with a fluorescent dye is investigated for imaging applications such as cell uptake and biodistribution. Batch emulsion polymerization (BEP) and monomer‐starved semi‐batch emulsion polymerization (MSSEP) are adopted using SDS. Fluorescent properties are added to these NPs using Rhodamine‐B (RhB) as a fluorescent dye covalently bonded to 2‐hyroxyethyl‐acrylate. The resulting HEMA‐RhB monomer is copolymerized with MMA via BEP and MSSEP to synthesize fluorescent NPs. Subsequently, SDS is substituted with a biocompatible surfactant, Tween80, through ionic‐exchange resins. ζ‐Potential measurements confirmed the complete surfactant exchange that leads to biocompatible fluorescent NPs with tunable size and narrow size distribution. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>